Fractography analysis and fatigue strength of carbon fiber/RTM6 laminates - Hilario Cioffi, Maria Odila [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Marin Camargo, Jose Andre [UNESP]; Rezende, Mirabel Cerqueira; Ortiz, Edmundo C.; Ambrosio, Luigi (Elsevier B.V. Sa, 2010)
The Brazilian industry has shown interest in resin transfer molding process (RTM) to produce aeronautical structural frames with low cost. Literature shows such manufacturing process as adequate to produce simple geometry polymer composite airframes, fairly thickness, requiring high quality of finish without manufacturing scale limitations. An experimental methodology regarding a carbon epoxy composites landing gear sub-component has been developed and a 7050 T7451 stalk was selected to be produced by RTM process. Fatigue sub-scale specimens of intermediate modulus carbon fiber non-crimp multiaxial reinforcement and epoxy mono-component system composite were produced according to ASTM D3039. Axial fatigue tests were carried out according to ASTM D3479 with a sinusoidal load of 10 Hz and load ratio R=0.1. Delamination process occurred independently on the applied load. In order to confirm the replacement advantages, composite properties were compared to those of anodized 7050 T7451 aluminum alloy. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; Aluminum alloys; Composites; Fatigue